Cellular, Molecular and Clinical Aspects of Aortic Aneurysm-Vascular Physiology and Pathophysiology - Domagała, Dominika; Data, Krzysztof; Szyller, Hubert; Farzaneh, Maryam; Mozdziak, Paul; Woźniak, Sławomir; Zabel, Maciej; Dzięgiel, Piotr; Kempisty, Bartosz (Cells, 2024)
A disturbance of the structure of the aortic wall results in the formation of aortic aneurysm, which is characterized by a significant bulge on the vessel surface that may have consequences, such as distention and finally rupture. Abdominal aortic aneurysm (AAA) is a major pathological condition because it affects approximately 8% of elderly men and 1.5% of elderly women. The pathogenesis of AAA involves multiple interlocking mechanisms, including inflammation, immune cell activation, protein degradation and cellular malalignments. The expression of inflammatory factors, such as cytokines and chemokines, induce the infiltration of inflammatory cells into the wall of the aorta, including macrophages, natural killer cells (NK cells) and T and B lymphocytes. Protein degradation occurs with a high expression not only of matrix metalloproteinases (MMPs) but also of neutrophil gelatinase-associated lipocalin (NGAL), interferon gamma (IFN-γ) and chymases. The loss of extracellular matrix (ECM) due to cell apoptosis and phenotype switching reduces tissue density and may contribute to AAA. It is important to consider the key mechanisms of initiating and promoting AAA to achieve better preventative and therapeutic outcomes.
Keywords: aneurysma břišní aorty; aorta; Cytokines; lidé; Apoptosis; Phenotype; cytokiny; fenotyp; Aortic Aneurysm, Abdominal; Humans; Aged; senioři; Male; mužské pohlaví; apoptóza; Aorta; ženské pohlaví; Female